How is this possible ?
plz figure out and re-write the formula.
NCERT galt ho skti h?? ●_●
Attachments:
![](https://hi-static.z-dn.net/files/d4e/25146417c38ede14da773c8148287349.jpg)
Answers
Answered by
4
Step-by-step explanation:
1.
∫ dx/√1 - x²
Let x = sin u, then dx = cos u du.
==> ∫(1/√1 - sin²u) * cos u du
=> ∫(1/√cos²u) * cos u du
=> ∫(1/cosu) * cos u du
=> ∫1 du
=> u + C
=> sin⁻¹x + C
(2)
Derivative of d/dx cos⁻¹(x) = -1/√1 - x²
It can also be written as,
==> ∫dx/√1 - x² = -cos⁻¹ x + C
#Hope my answer helped you!
Answered by
2
Answer:
Hope the above attachment helps you......alien ji....xd
Attachments:
![](https://hi-static.z-dn.net/files/d8a/cad8674c5ed8aafdd5dbd060f1a3832e.jpg)
![](https://hi-static.z-dn.net/files/d80/121811cbf7db20429e9f19adbad0a14b.jpg)
Similar questions